ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KOPI BUBUK DI UMKM KOPI KAPAL LAMPUNG - Haryani, Nadila Septyana; Budiraharjo, Kustopo; Handayani, Migie (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Micro, Small and Medium Enterprises (MSMEs) Kopi Kapal Lampung is an MSME in Bandar Lampung City that sells ground coffee with the Kapal Lampung stamp. The demand for Kapal Lampung ground coffee tends to fluctuate, so it is necessary to know the factors that influence the demand for Kapal Lampung ground coffee on household scale consumers. This study aims to analyze the factors that influence the demand for Kapal Lampung powdered coffee on household scale consumers at MSME Kopi Kapal Lampung and analyze the elasticity of demand for Kapal Lampung powdered coffee. This research was carried out in October 2021, which was located at the UMKM Kopi Kapal Lampung. Determination of the location is determined intentionally (purposive). The method used in this study is a survey method with the determination of respondents as many as 100 people using non-probability sampling technique by purposive accidental sampling. Methods of data analysis with quantitative descriptive analysis using multiple linear regression analysis. Based on the results of the study, it was found that the variables of income, number of family members, frequency of consumption, product prices and consumer tastes simultaneously had a very significant effect on coffee demand. The variables of income, consumption frequency and consumer tastes have a partial effect on coffee demand. The number of family members and the price of the product have no partial effect on the demand for coffee. The price elasticity and income elasticity are inelastic to the demand for ground coffee with Kapal Lampung stamp. The Lampung Ship's powdered coffee product is classified as normal goods.